ByzRev 02.2020.022: Gregory Palamas. The Hesychast Controversy and the Debate with Islam. Documents relating to Gregory Palamas. Translated with an introduction and notes by Norman Russell: (Translated Texts for Byzantinists 8). Liverpool: Liverpool University Press 2020. - Greis, Ralph (The Byzantine Review, 2020)
Gregory Palamas. The Hesychast Controversy and the Debate with Islam. Documents relating to Gregory Palamas. Translated with an introduction and notes by Norman Russell (Translated Texts for Byzantinists 8). Liverpool: Liverpool University Press 2020. xii, 488 pp. – ISBN: 978-1-78962-153-2 (£ 125)